The Dark Side of High-Fliers: The Dark Triad, High-Flier Traits, Engagement, and Subjective Success - Furnham, Adrian; Treglown, Luke (Frontiers in Psychology, 2021)
In all, 290 working adults completed questionnaires assessing their “high potential” personality traits (HPTI), their dark-triad traits, job engagement and self-rated success at work. The data showed that the three dark-triad traits (Narcissism, Psychopathy, Machiavellianism) were systematically and significantly correlated with HPTI traits Adjustment/Neuroticism, Tolerance of Ambiguity and Conscientiousness. Three HPTI traits, namely Curiosity, Conscientiousness and Courage, were systematically positively correlated with all three engagement measures. Narcissism was strongly related to all measures of engagement. Stable, Courageous, Narcissistic males, rated their success highest. Job engagement mediated between high-flyer and dark-side traits and success ratings. Implications and limitations are discussed.